2020
DOI: 10.1038/s41598-020-71653-z
|View full text |Cite
|
Sign up to set email alerts
|

The type VII secretion system protects Staphylococcus aureus against antimicrobial host fatty acids

Abstract: The Staphylococcus aureus type VII secretion system (T7SS) exports several proteins that are pivotal for bacterial virulence. The mechanisms underlying T7SS-mediated staphylococcal survival during infection nevertheless remain unclear. Here we report that S. aureus lacking T7SS components are more susceptible to host-derived antimicrobial fatty acids. Unsaturated fatty acids such as linoleic acid (LA) elicited an increased inhibition of S. aureus mutants lacking T7SS effectors EsxC, EsxA and EsxB, or the membr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 67 publications
1
23
0
Order By: Relevance
“…In addition to ica locus, the presence of clfA, clfB, and epbs genes initiates the biofilm formation (Ghasemian et al, 2015), however in the present study, the SA H27 isolate carried clfA, and epbs genes and showed strong biofilm formation in our previous study (Naorem et al, 2020) compared to other isolates while SA G8 and SA H32 isolates carried clfA, clfB, and epbs genes though their biofilm formation was relatively low, suggesting that presence or absence of such genes have no significant in biofilm formation. A recent study reported that sdrC mutant exhibited significantly inhibited biofilm formation (Chen et al, 2019) and the expression of the ica operon and sdrC are highly responsive to biofilm formation (Shin et al, 2013). Our study revealed the sequence variation in sdrC in Hungarian isolates, this variation might influence the biofilm formation.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…In addition to ica locus, the presence of clfA, clfB, and epbs genes initiates the biofilm formation (Ghasemian et al, 2015), however in the present study, the SA H27 isolate carried clfA, and epbs genes and showed strong biofilm formation in our previous study (Naorem et al, 2020) compared to other isolates while SA G8 and SA H32 isolates carried clfA, clfB, and epbs genes though their biofilm formation was relatively low, suggesting that presence or absence of such genes have no significant in biofilm formation. A recent study reported that sdrC mutant exhibited significantly inhibited biofilm formation (Chen et al, 2019) and the expression of the ica operon and sdrC are highly responsive to biofilm formation (Shin et al, 2013). Our study revealed the sequence variation in sdrC in Hungarian isolates, this variation might influence the biofilm formation.…”
Section: Discussionmentioning
confidence: 50%
“…Type VII secretion system (T7SS) was present in Germany isolates (Fig. 3A) and promoting them to persist in their hosts (Tchoupa et al, 2019). The esxA and esxB gene show a significant role in the distribution and colonization of S. aureus, and activation of the cell-mediated immune responses, boost the pathogenesis (Burts et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Most ST9 genomes carried hemolysin genes, including hlb (91.1%; n = 174), hld (99.5%; n = 190), hlgA (100%; n = 191), hlgB (100%; n = 191), hlgC (100%; n = 191), and hly/hla (99.5%; n = 190), which have been shown to play an important role in skin colonization and infection ( 18 ). ST9 genomes also encoded a pivotal virulence factor, the type 7 secretion system (T7SS), which has been found to contribute to membrane integrity and homeostasis in the presence of antimicrobial fatty acids ( 19 ). Identified genes of T7SS corresponded to four membrane proteins ( esaA , essA , essB , and essC ), one cytosolic protein ( esaB ), and two effector proteins ( esxA and esxB ).…”
Section: Resultsmentioning
confidence: 99%
“…5B ). For example, cap8A, cap8B, cap8C, cap8D, cap8E, cap8F , and cap8G involve in the biosynthesis of capsule, which contributes to the virulence and antiphagocytosis of S. aureus (24-26); clpP1, clpP2 and clpC participate in the encoding of Clp chaperones, ATPases and proteases; both of these proteins are central in stress survival, virulence and biofilm formation of S. aureus (27, 28); the product of katA (catalase enzyme KatA) has a capacity to decompose hydrogen peroxide, which is a reactive oxygen intermediate and is indispensable for the bactericidal activity of phagocytes (29); esxA encodes the type VII secretion system (T7SS) effector protein EsxA which is pivotal for bacterial virulence (30); the heat shock protein coding gene htpB encodes a 60-kDa chaperonin with an essential function as mediators of protein folding; this protein is important in bacterial pathogenesis and could mediate bacterial attachment to and invasion of host cells (31, 32); icaR is a known biofilm regulator gene in Staphylococcus and its upregulation contributes to the biofilm formation (33); cpsK encodes the teichoic acids export ABC transporter permease subunit TagG which is beneficial for the export of bacterial polysaccharides-wall teichoic acids, thereby contributing to the polysaccharides production (34). In addition, the upregulated-expressed genes induced by the integration of PHB21 genome in the lysogenic strain SA14 + are related to several KEGG pathways that have previously been reported to have important roles in the biofilm formation, stress tolerance, and pathogenesis of Staphylococcus (21, 22) ( Figs 5C∼E ).…”
Section: Discussionmentioning
confidence: 99%